Generation of a human induced pluripotent stem cell line (LZUSHi003-A) from peripheral mononuclear cells of a patient carrying the c.3682delG mutation in the dystrophin gene - Jie Shi; Jiao Yang; Huijun Gao; Lan Yang; Yinpeng Zhang; Ansheng Zhao; Rui Yang; Zhonghong Xiong; Jing Yang; Bei Gao (Stem Cell Research)
Duchenne muscular dystrophy (DMD) is characterized by progressive muscle degeneration and is caused by mutations in the dystrophin gene. Here, we used Sendai virus to generate a human induced pluripotent stem cell line, LZUSHi003-A, from the peripheral mononuclear cells of a 13-year-old male patient carrying the DMD gene mutation c.3682delG. The LZUSHi003-A cell line retained this mutation, while expressing pluripotency markers. Additionally, it demonstrated a normal karyotype and could differentiate into three embryonic germ layers.